Chest imaging : an algorithmic approach to learning - Folio, Les R. (Springer New York, 2012)
Chest Imaging offers a concise introduction to radiographic chest procedures through a methodical, pattern-driven approach. Filled with high-resolution images, this practical guide provides a thorough explanation of key terms, concepts, and procedures useful for medical students, radiology residents, and others to learn the basics of the plain film chest x-ray (CXR). The book includes a companion online resource at www.robochest.com designed for use in combination to provide students with numerous examples of clinically significant abnormalities commonly detected on CXRs. Chapters present a structured lexicon to teach students to reproducibly describe radiographic abnormalities of the chest detected on CXRs. Topics present specific combinations of distinct radiographic findings in relation to classes and groupings of pathological etiologies of those findings. Recognizing individual findings and identifying their combination or lack of combination with other findings allows students to learn effective differential diagnoses. Chest Imaging includes hundreds of radiographs, CTs, graphics, mnemonics, differentials, and analogous models to help teach otherwise complex processes and radiographic principles.